MODELS AND ALGORITHMS OF DECISION SUPPORT SYSTEMS IN CORPORATE INFORMATION LIBRARY SYSTEMS (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
Decision Support Systems (DSS) are critical tools that assist decision-makers in handling complex tasks by providing relevant data, analysis, and forecasting models. In corporate information and library systems, DSS play a pivotal role in streamlining processes such as resource allocation, customer relationship management, inventory control, and literature retrieval. This article explores the theoretical foundations, models, and algorithms of DSS in these domains, offering insights into the methods used for decision-making in dynamic business environments and academic libraries. Furthermore, it highlights the integration of these systems with modern technologies such as artificial intelligence, machine learning, and big data analytics. The research was carried out within the framework of the practical project No. ALM-202310132635 "Smart Academy - creation of an integrated information-educational platform" supported by the Innovative Development Agency under the Ministry of Higher Education, Science and Innovation.
Keywords: algorithm; decision support system; library system; expert system; fuzzy logic; tf-idf